1983
DOI: 10.1017/s0031182000057231
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to induce protective immunity in hamsters against infection by a liver fluke of man (Opisthorchis viverrini)

Abstract: The development of acquired resistance in opisthorchiasis was studied in hamsters experimentally infected with Opisthorchis viverrini. The induction of protective immunity was attempted by first exposing adult female golden Syrian hamsters to 1, 2 or 3 doses of infective metacercariae obtained from naturally infected cyprinoid fishes and then reinfecting them with 80 metacercariae. In other experiments, animals that were infected with 50 metacercariae were treated with praziquantel prior to being rechallenged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Flavell (1982) reported that hamsters acquire resistance to O. viverrini, and that this results in a significant worm burden reduction (Flavell, 1982), suggesting that prior infection results in a significant reduction in the faecal egg during a subsequent infection. On the other hand, Sirisinha et al (1983) demonstrated that a prior infection failed to induce significant protection against reinfection by O. viverrini in hamsters (Sirisinha et al, 1983). A lack of protection was also noted in animals reinfected or superinfected several times with small doses of metacercariae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavell (1982) reported that hamsters acquire resistance to O. viverrini, and that this results in a significant worm burden reduction (Flavell, 1982), suggesting that prior infection results in a significant reduction in the faecal egg during a subsequent infection. On the other hand, Sirisinha et al (1983) demonstrated that a prior infection failed to induce significant protection against reinfection by O. viverrini in hamsters (Sirisinha et al, 1983). A lack of protection was also noted in animals reinfected or superinfected several times with small doses of metacercariae.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, results on resistance to reinfection in hamsters infected with O. viverrini, another liver fluke closely related with C. sinensis, are controversial (Flavell, 1982;Sirisinha et al, 1983). Flavell (1982) reported that hamsters acquire resistance to O. viverrini, and that this results in a significant worm burden reduction (Flavell, 1982), suggesting that prior infection results in a significant reduction in the faecal egg during a subsequent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies reported contradictory data on the protective immunity against reinfection with O. viverrini in hamsters. Prior infection with O. viverrini did not protect hamsters against reinfection by the same parasite (Sirisinha et al, 1983), and adoptive transfer of spleen cells and sera from infected hamsters produced a moderate, but insignificant reduction in the worm burden in recipient hamsters (Flavell et al, 1980).…”
mentioning
confidence: 88%
“…The anthelmintic, praziquantel, has been more widely used than any other drug for treatment of OV infection because of its apparent effectiveness and the short time for the healing of damage done by OV following its eradication (Boonmars et al, 2007). However, while praziqantel seems effective against an existing infection with cure rates reported to be as high as 96% and 100% (Soukhathammavong et al, 2011), there is no evidence of any protective immunity against re-infection (Sirisinha et al, 1983;Upatham et al, 1988) and repeated dosing with the anthelmintic is necessary for those re-exposed to infection.…”
Section: Infection With Opisthorchis Viverrini and Use Of Praziquantementioning
confidence: 99%